Resurrection and Parousia : a traditio-historical study of Paul's eschatology in I Corinthians 15 - Holleman, Joost. (Novum Testamentum, Supplements, 1996)
This is a traditio-historical study of three ideas concerning the eschatological resurrection which Paul brings forward in 1 Corinthians 15:20-23: (a) Jesus' resurrection forms the beginning of the eschatological resurrection; (b) the eschatological resurrection will take place through participation in Jesus' resurrection; (c) the eschatological resurrection will take place at the time of Jesus' parousia. The three ideas are investigated in the following way. Firstly, their occurrence and function in Paul is set out, subsequently their origin is reconstructed, and, finally, analogous Jewish concepts are compared. A critical review of earlier research on these ideas and a literary and historical exegesis of the relevant sections of 1 Corinthians 15 precede the investigations.